Use of pectoralis major myocutaneous flap for resurfacing the soft tissue defects of head and neck - Rampukar Chaudhary; Md Sohaib Akhtar; Lalit Mohan Bariar; Mohammed Fahud Khurram (Wolters Kluwer Medknow Publications, 2014)
Aims and Objectives: The aim was to evaluate the feasibility of pectoralis major myocutaneous (PMMC) flap in reconstruction of defects in the head and neck region. The study also outlines types of other tissue required, the donor site morbidity and the technical details of the operative procedure. Materials and Methods: This was a retrospective study undertaken on patient of soft tissue defect of head and neck region either traumatic or after resection of the tumor admitted to author's center. A total of 62 patients was included, among them, 59 patients were of malignancy and 3 patients were of traumatic injury to face. All the patients of malignancy underwent wide local excision of the tumor with modified radical neck dissection type III. After resection, the resultant defect was covered with pectoralis major myocutaneus flap (PMMF) with or without deltopectoral (DP) flap or forehead flap (PMMF or PMMF + DP/forehead flap). The operating time was noted from elevation of the flap to completion of flap insetting. Results: All the flaps survived uneventfully except 4, out of this 1 developed total flap necrosis, 1 partial flap necrosis and 2 experienced epidermolysis. Orocutaneous fistula was noted in 3 patients in initial days and after removal of the intraoral suture the fistula spontaneously resolved in all cases. Conclusion: It was concluded that PMMC is the highly versatile and reliable flap with an excellent vascularity, wide arc of rotation, large flap dimension, easy to harvest, economical and with minimal complications.